Association of ambulance and helicopter response times with patient survival: A systematic literature review and meta-analysis - Peter Martin Hansen; Martine Siw Nielsen; Marius Rehn; Annmarie Lassen; Anders Perner; Søren Mikkelsen; Anne Craveiro Brøchner (PLoS ONE, 2025)
Background Only sparse scientific evidence supports the notion that the shortest possible response time relates to improved patient outcomes in acute conditions, other than out-of-hospital cardiac arrest and trauma. Confounders such as bidirectional causality and confounding by indication may influence patient-centered outcomes, which may prevent actionable conclusions from literature reviews. The purpose of the systematic literature review was to assess current evidence on association, if any, between ambulance and helicopter response times and survival in all patient categories treated by ambulance or helicopter services. Methods The systematic search was conducted in MEDLINE, Cochrane Library, EMBASE, CINAHL, Scopus, and Clinical Trial Registries. All study designs and settings identified as relevant to the topic were eligible. The investigators retrieved data from a predefined template and extracted data from a predefined template. Two reviewers worked independently, and conflicts were resolved by a third reviewer. The researchers used PRISMA guidelines for abstracting data and GRADE methodology for assessing data quality and validity. As per study protocol, the primary study outcome was patient survival, and the main measurement was response time for emergency medical services vehicles. Results The investigators included 115 studies that in total included 691,056 patients, comprising patients with out-of-hospital cardiac arrest, trauma, drownings, and including both adults and children in various settings. The overall median survival rate was 11.5% (IQR 5.2; 25.8). Response time varied between 1.10 and 48.62 minutes. The predefined domains and items of interest were accounted for in 46.7% of the included literature. In a meta-analysis of sub-groups, there was a positive correlation in selected populations. Certainty of evidence was very low as per GRADE methodology. Conclusions This systematic review and meta-analysis found lack of evidence to infer an association between the EMS response time and patient survival, with very low certainty of evidence. The investigators found substantive research and knowledge gaps. Therefore, no actionable conclusions can be made from this systematic review.